2013
DOI: 10.1055/s-0033-1333833
|View full text |Cite
|
Sign up to set email alerts
|

Upper Lid Blepharoplasty

Abstract: Blepharoplasty is one of the most commonly performed aesthetic procedures in the realm of aging face surgery. Although not prohibitively challenging from a technical perspective, upper blepharoplasty remains a surgical procedure that requires comprehensive knowledge of intricate eyelid anatomy. In addition, the surgeon must pay attention to adjacent areas, notably the brow, which may also need to be addressed to achieve optimal results. These features, along with changes associated with aging and important asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…Brow ptosis and asym-metry are relatively common among this population, and discussing brow position with patients is important for determining the appropriate surgical or nonsurgical management. [3][4][5][6][7][8] In the current study, more than 80% were found to have some degree of brow ptosis and almost 90% had brow asymmetry. This is similar to previous reports; MacDonald et al reported 93% of their patients evaluated for blepharoplasty to have measurable brow asymmetry.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Brow ptosis and asym-metry are relatively common among this population, and discussing brow position with patients is important for determining the appropriate surgical or nonsurgical management. [3][4][5][6][7][8] In the current study, more than 80% were found to have some degree of brow ptosis and almost 90% had brow asymmetry. This is similar to previous reports; MacDonald et al reported 93% of their patients evaluated for blepharoplasty to have measurable brow asymmetry.…”
Section: Discussionsupporting
confidence: 42%
“…3,4 Brow ptosis and asymmetry can be present; a recent study by Macdonald et al specifically demonstrated a high percentage of brow asymmetry in patients being evaluated for blepharoplasty. [3][4][5][6][7][8] Brow ptosis and brow asymmetry can lead to a perception of an aging face as well as an aesthetically unattractive appearance. The idea of beauty is often thought to include relative symmetry between the two sides of the face.…”
mentioning
confidence: 99%
“…Distintas técnicas difieren en distintos aspectos, por ejemplo, la resección o no de músculo, respetar o no la grasa, e inclusive utilizar el láser de CO 2 dentro del procedimiento 13,14 . Los estudios que más han influido en este cambio de postura quirúrgica son los que han indagado en el proceso de envejecimiento de esta área y la anatomía periorbitaria, llevando con ello a mejores resultados estéticos en conjunto con una mayor satisfacción del paciente y cirujano [15][16][17] .…”
Section: Discussionunclassified
“…Presurgical lagophthalmos or patients with Grave's ophthalmopathy/ocular proptosis can develop severe scleral show and corneal damage if undergoing upper lid blepharoplasty. 9,10 Extensive documentation of a presurgical visual assessment is vital to avoid any question of visual changes after the procedure. In addition, insurance approval is predicated on such an exam if this procedure is to ameliorate visual field loss from dermatochalasis and is not purely cosmetic in nature.…”
Section: Preoperative Evaluationmentioning
confidence: 99%